Light grazing facilitates carbon accumulation in subsoil in Chinese grasslands: A meta‐analysis - Zhi‐Yun Jiang; Zhong‐Min Hu; Derrick Y. F. Lai; Dao‐Rui Han; Mei Wang; Min Liu; Meng Zhang; Ming‐Yan Guo (Global Change Biology, 2020)
Grazing by livestock greatly affects the soil carbon (C) cycle in grassland ecosystems. However, the effects of grazing at different intensities and durations on the dynamics of soil C in its subsoil layers are not clearly understood. Here, we compiled data from 78 sites (in total 122 published studies) to examine the effects of varying grazing intensities and durations on soil C content at different depths for grasslands in China. Our meta‐analysis revealed that grazing led to an overall decrease in soil C content and productivity of above‐ground vegetation (e.g., above‐ground biomass and litter) but an increase in below‐ground biomass. Specifically, the effects of grazing on soil C content became less negative or even positive with increasing soil depths. An increase of soil C content was consequently found under light grazing (LG), although soil C content still decreased under moderate and heavy grazing. The increase in soil C content under LG could be largely attributed to the increase of soil C content in subsoil layers (>20 cm), despite that soil C content in surface soil layer (0–20 cm) decreased. Moreover, the magnitude of increase in soil C content under LG in subsoil layers increased with grazing duration. A possible reason of the increase in soil C content in the subsoil layers was due to the increases in below‐ground biomass. Our study highlights that LG may modify the allocation of C input and promote its accumulation in subsoil layers, thus offsetting the negative impact of grazing on surface soil C content, a finding that has significant implications for C sequestration in grasslands.

Hydrogeochemical and isotopic characteristics of groundwater in Xinchang preselected site and their implications - Zhichao Zhou; Ju Wang; Rui Su; Yonghai Guo; Jingbo Zhao; Ming Zhang; Ruili Ji; Yanan Li; Jiebiao Li (Environmental Science and Pollution Research, 2020)

Distribution and risk of mercury in the sediments of mangroves along South China Coast - Rui-Fei Ma; Hao Cheng; Aniefiok Inyang; Ming Wang; You-Shao Wang (Ecotoxicology, 2020)

Spatial Variation in Thermal Stress Experienced by Barnacles on Rocky Shores: The Interplay Between Geographic Variation, Tidal Cycles and Microhabitat Temperatures - Hui-Yu Wang; Ling Ming Tsang; Fernando P. Lima; Rui Seabra; Monthon Ganmanee; Gray A. Williams; Benny K. K. Chan (Frontiers in Marine Science, 2020)

The role of miRNA-155 in monocrotaline-induced pulmonary arterial hypertension through c-Fos/NLRP3/caspase-1 - Shou-Dong Chai; Zhen-Kun Li; Rui Liu; Tao Liu; Ming-Feng Dong; Pei-Zhe Tang; Jian-Tang Wang; Sheng-Jun Ma (Molecular & Cellular Toxicology, 2020)

Drought characteristics and its impact on changes in surface vegetation from 1981 to 2015 in the Yangtze River Basin, China - Weixia Jiang; Lunche Wang; Lan Feng; Ming Zhang; Rui Yao (International Journal of Climatology, 2020)
Located in the subtropical monsoon climate area of China, the Yangtze River Basin (YRB) had been frequently affected by drought events recently. Based on standardized precipitation evapotranspiration Index (SPEI) and enhanced vegetation index (EVI), the characteristics of drought in the YRB and the influence of drought on vegetation in different seasons were investigated by maximum correlation ( R max ) between 1981 and 2015. The results showed that: (a) Droughts occurred frequently but had no obvious regularity in the YRB from 1981 to 2015. The drought intensity in autumn and winter were slightly higher than that in spring and summer. The autumn droughts in Sichuan Basin were the most serious, followed by the spring droughts in the middle and lower reaches of the YRB; (b) Annual SPEI series at 102 stations exhibited a downward trend and 72 stations exhibited an upward trend. There was no station showing a significant downward trend and two stations showing a significant upward trend. There was a drying trend in autumn and winter, and a wetting trend in spring and summer. The eastern area of the YRB shows a more arid trend in spring and autumn, as well as in the southwest in winter; (c) 90% of YRB showed a significant positive correlation ( p

Mapping and characterization of major QTL for spike traits in common wheat - Cheng-Hao Kuang; Xiao-Fang Zhao; Ke Yang; Zhi-Peng Zhang; Li Ding; Zhi-En Pu; Jian Ma; Qian-Tao Jiang; Guo-Yue Chen; Ji-Rui Wang; Yu-Ming Wei; You-Liang Zheng; et al. (Physiology and Molecular Biology of Plants, 2020)

Characterization of a Rapeseed Anthocyanin-More Mutant with Enhanced Resistance to Sclerotinia sclerotiorum - Rui Liu; Li-Na Ding; Ming Li; Wei Cao; Yu-Kang Wang; Wei-Jie Wang; Yan-Kun Yu; Zheng Wang; Ke-Ming Zhu; Xiao-Li Tan (Journal of Plant Growth Regulation, 2020)

Clinical strategies for differentiating IgG4-related cholecystitis from gallbladder carcinoma to avoid unnecessary surgical resection - Rui Zhang; Hao-Ming Lin; Zhao-Xi Cai; Su-Juan Du; Hong Zeng; Lei-Bo Xu; Jie Wang; Chao Liu (Science China Life Sciences, 2020)

Uptake and accumulation of pentachloronitrobenzene in pak choi and the human health risk - Ming Li; Guanghui Xu; Rui Yu; Yang Wang; Yong Yu (Environmental Geochemistry and Health, 2020)

Preparation and In vitro Evaluation of FDM 3D-Printed Ellipsoid-Shaped Gastric Floating Tablets with Low Infill Percentages - Di Chen; Xiang-Yu Xu; Rui Li; Gen-Ao Zang; Yue Zhang; Ming-Rui Wang; Meng-Fei Xiong; Jia-Rui Xu; Ting Wang; Hui Fu; Qin Hu; Bin Wu; et al. (AAPS PharmSciTech, 2020)